MATLAB A Fundamental Tool for Scientific Computing and Engineering Applications - Volume 1 - Katsikis, Vasilios N. (IntechOpen, 2012)
This is the first book in a three-volume series deploying MATLAB-based applications in almost every branch of science. This volume, presents interesting topics from different areas of engineering, signal and image processing based on the MATLAB environment. The book consists of 20 excellent, insightful articles and the readers will find the results very useful to their work. This collection of high quality articles, refers to a large range of professional fields and may be used for scientific, engineering and educational purposes.